Motivasi Wisatawan Berkunjung ke The Sila’s Agrotourism di Desa Candikuning, Kecamatan Baturiti, Kabupaten Tabanan - LEDI INUSUKA GINTING; I GDE PITANA; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Tourist Motivation Visiting The Sila’s Agrotourism in Candikuning Village, Baturiti Sub-District, Tabanan Regency The Sila’s Agrotourism is one of the most popular agrotourism in Bali with a capital-based agrotourism model. The purpose of the study was to analyze the characteristics of tourists and the motivation of tourists visiting The Sila’s Agrotourism. To achieve this goal, this research used descriptive analysis method. The number of samples was 100 people using accidental sampling method.The results of this study indicate that tourists visiting The Sila’s Agrotourism have various characteristics, seen from the place of origin, gender, age, occupation, sources of information and how to visit. Tourists visiting The Sila’s Agrotourism are generally dominated by domestic tourists. In addition, the biggest motivation of tourists visiting The Sila's Agrotourism is physical motivation (85.8%), followed by social motivation(83.75%), fantasy motivation (74.5%) and the last is cultural motivation (51%). The most dominant factor in physical motivation is to find a calm atmosphere and enjoy the cool natural atmosphere.